Prediction of Financial Distress by Zmijewski’s X-Score Model in Selected Indian Iron and Steel Companies - Arshe AZAM; Syed Khaja SAFIUDDIN (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
The study delves into the intricate realm of financial distress prediction within the Indian Iron and Steel sector, employing Zmijewski's X-Score Model. The analysis encompasses five prominent companies – Jayaswal Neco Industries Ltd., Incredible Industries Ltd., Sarda Energy & Minerals Ltd., Kritika Wires Ltd., and Hariom Pipe Industries Ltd. – over five years from 2018 to 2022. The research uncovers nuanced insights into the financial health of these companies. Jayaswal Neco Industries Ltd., Incredible Industries Ltd., and Kritika Wires Ltd. showcase stability or improvement, indicating lower risks of financial distress. Conversely, Sarda Energy & Minerals Ltd. faces heightened risk, notably in 2022, while Hariom Pipe Industries Ltd. consistently exhibits financial vulnerability, worsening in the same year. The study employs robust statistical analyses, including multivariate tests and between-model effects analysis, revealing that specific financial ratios significantly impact Kritika Wires Ltd.'s stability. However, the complexity of financial distress becomes evident as other companies do not show significant impacts, underscoring the necessity for a nuanced understanding of diverse business dynamics. This research provides in-depth insights into financial distress prediction in the Indian Iron and Steel sector, offering valuable implications for industry practitioners and policymakers. By comprehending the complexities and adopting effective predictive models, companies can proactively manage risks, ensuring stability and contributing to overall economic growth.